Gereja Mandiri Berdasarkan Kitab Filipi: Kajian Teologis dan Aplikasi Praktis Bagi Gereja Global Masa Kini - happy yusack; Riwono Riwono (Sekolah Tinggi Teologi Berita Hidup, 2026)
The concept of the “self-governing church” has become a key topic in contemporary theology, especially as the church faces the challenges of globalization, financial dependence, and changes in mission. The Book of Philippians, known as the Apostle Paul’s “Letter of Joy,” contains theological values relevant to building a mature, self-governing, and missional church. Amid shifting mission paradigms and global economic challenges, the church often finds itself trapped in dependency or isolation. The Book of Philippians offers a model of a mature local church, financially and structurally self-reliant, yet still remaining within apostolic relationships and a global mission network. This study aims to: first, examine the concept of an autonomous church based on the theological exegesis of the Book of Philippians; second, identify Paul’s ecclesiological principles relevant to the global church today; third, formulate practical applications for the development of an autonomous church that remains faithful to orthodoxy and global mission. Using a qualitative-descriptive approach and biblical exegesis, this study found that autonomy in the Book of Philippians does not refer to absolute autonomy, but rather to Christ-centered interdependence. The results of the study indicate that the church in Philippi exhibits the characteristics of a healthy self-governing church: active financial participation, structured local leadership, global missionary solidarity, Christological unity, and a mature spirituality of suffering. The church in Philippi does not. Konsep “gereja mandiri” telah menjadi topik penting dalam teologi masa kini, terutama saat gereja menghadapi tantangan globalisasi, ketergantungan keuangan, dan perubahan dalam misi. Kitab Filipi, yang dikenal sebagai surat sukacita Rasul Paulus, mengandung nilai-nilai teologis yang relevan untuk membangun gereja yang dewasa, mandiri, dan misioner. Penelitian ini melalui kajian eksegetis terhadap teks Filipi menyotoyi tiga hal utama: pertama, kemandirian gereja bukan hanya soal otonomi institusi, tetapi juga kedewasaan rohani yang berakar pada hubungan dengan Kristus; kedua, prinsip kemandirian gereja meliputi spiritualitas yang berpusat pada Kristus, pengelolaan yang bertanggung jawab, dan keterlibatan aktif dalam misi global; ketiga, gereja mandiri masa kini perlu menunjukkan kemandirian tidak hanya dalam hal keuangan, tetapi juga dalam visi, teologi, dan praktik pelayannya.